PROPOSAL AND TEST-RETEST RELIABILITY OF A SCALE FOR CERVICAL, THORACIC, AND LUMBAR SPINE PAIN IN BRAZILIAN YOUNG PEOPLE - Gustavo Aires de Arruda; Diogo Henrique Constantino Coledam; Arli Ramos de Oliveira; Fernanda dos Santos Neri; João Paulo de Aguiar Greca; Jefferson Rosa Cardoso (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To propose and analyze the test-retest reliability of an instrument to verify the presence and intensity of pain in the cervical, thoracic and lumbar spine in Brazilian young people. Methods: This reliability study enrolled a sample of 458 participants (13 to 20 years). Two groups were formed for each sex according to the range of days for the test-retest (10±3 and 28±2 days). For analysis of spinal pain, a drawing of the human body with cervical, thoracic and lumbar spine areas delimited was presented. The following question was presented: during a normal day, do you feel pain in any of these regions of your spine? If so, what is the intensity from 0 to 10 (mark on the line)? The starting point, with the number 0, corresponded to no pain, and the number 10 to severe pain. The agreement of frequency and of intensity of pain was verified by Kappa test and Bland-Altman plot, respectively. Results: Intraclass correlation coefficients ranged from 0.71 (confidence interval of 95% - 95%CI - 0.59-0.79) to 0.94 (95%CI 0.90-0.96). The results concerning the agreement of pain scores showed the mean differences to be close to 0, and the largest mean difference was -0.40 (95%CI -5.14-4.34). The agreement in reported pain ranged from 72.2 (Kappa 0.43; 95%CI 0.28-0.58) to 90.1% (Kappa 0.76; 95%CI 0.60-0.92). Conclusions: This instrument was shown to be a reliable manner to verify the pain in different regions of the spine in Brazilian young people.